Museum Boymans - van Beuningen : Afbeeldingen schilderijen. (Rotterdam : Museum Boijmans Van Beuningen Rotterdam, 1959)
Chagall, Marc ; van Dongen, Kees ; Dufy, Raoul ; Ensor, James ; Gauguin, Paul ; van Gogh, Vincent ; Kandinsky, Wassily ; Kokoschka, Oskar ; Marc, Franz ; Marquet, Albert ; Matisse, Henri ; Munch, Edvard ; Permeke, Constant ; Picasso, Pablo ; Renoir, Auguste ; Signac, Paul ; Sisley, Alfred ; Wouters, Rik
biografie
Dutch-English-German
boek